In situ transmission electron microscopy for magnetic nanostructures - Ngo, Duc-The; Kuhn, Luise Theil (Advances in natural sciences. Nanoscience and nanotechnology, 2016)
Nanomagnetism is a subject of great interest because of both application and fundamental aspects in which understanding of the physical and electromagnetic structure of magnetic nanostructures is essential to explore the magnetic properties. Transmission electron microscopy (TEM) is a powerful tool that allows understanding of both physical structure and micromagnetic structure of the thin samples at nanoscale. Among TEM techniques, in situ TEM is the state-of-the-art approach for imaging such structures in dynamic experiments, reconstructing a real-time nanoscale picture of the properties-structure correlation. This paper aims at reviewing and discussing in situ TEM magnetic imaging studies, including Lorentz microscopy and electron holography in TEM, applied to the research of magnetic nanostructures.